1974
DOI: 10.21273/jashs.99.2.121
|View full text |Cite
|
Sign up to set email alerts
|

Flower Bud Abscission in Pistachio (Pistacia vera L.) as Related to Fruit Development and Other Factors1

Abstract: In the pistachio, flower bud abscission is induced by seeded fruits during the summer, resulting in alternate bearing. The onset of abscission was not influenced by number of fruits, but rate and final percentage of abscission increased as fruit number increased. Twenty or more fruits per 1-year-old stem caused complete abscission. The course of abscission was correlated with rapid seed growth. Periodic defruiting indicated that induction of abscission preceded actual separation of buds by 28 days. A defoliati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
7
0

Year Published

1979
1979
2014
2014

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(7 citation statements)
references
References 1 publication
(1 reference statement)
0
7
0
Order By: Relevance
“…Crane and Nelson (1971) reported that the presence of fruit, and in particular seed growth, is responsible for inflorescent bud abscission and for inducing a biennial bearing pattern. The more fruit present on shoots or branches, the more buds drop (Porlingis 1974). Experiments with fruit removal resulted in inflorescent bud retention (Porlingis 1974, Wolpert and Ferguson 1990, Caruso et al 1992, Vemmos 2005.…”
Section: Introductionmentioning
confidence: 99%
“…Crane and Nelson (1971) reported that the presence of fruit, and in particular seed growth, is responsible for inflorescent bud abscission and for inducing a biennial bearing pattern. The more fruit present on shoots or branches, the more buds drop (Porlingis 1974). Experiments with fruit removal resulted in inflorescent bud retention (Porlingis 1974, Wolpert and Ferguson 1990, Caruso et al 1992, Vemmos 2005.…”
Section: Introductionmentioning
confidence: 99%
“…During that critical period, however, neither carbohydrate nor nitrogen levels in bark and wood of nut bearing branches were found to be appreciably different from those in nonbearing branches (6,7). Levels of nitrogen in buds of bearing trees were the same as those in buds of nonbearing trees (14). The information at hand, therefore indicates that unfavorable nutrition is not the primary cause of bud abscission.…”
mentioning
confidence: 65%
“…High levels of ABA in the fruit have been shown to be closely related to flower and young fruit abscission in lupine (18) and in cotton (8). As with pistachio (4,5,14), removal of develop ing fruits reduced abscission of flower buds in pea (12) and in soybean (11). It was shown recently that developing pea fruits brought about increases in ABA concentration in axillary buds and also induced abortion of young fruits (16,17).…”
mentioning
confidence: 99%
“…Flower bud abscission on current wood followed the general pattern established pre viously (6); that is, it began the last of June and was most intense during July and Au gust. Porlingis (11) reported that the induc tion of abscission preceded actual separation of the buds by 28 days. The beginning of the flower bud abscission period the last of June was preceded about 28 days earlier by the occurrence of zygote division.…”
mentioning
confidence: 99%